Development of an Interactive Digital E-Module Based on the ADDIE Model with Thaharah Material for PAI Students at UIN Palangka Raya as MTs Level Learners - Sindegi Afsana Oktaviani Ramadhan; Jasiah Jasiah (ANWARUL, 2025)
This study focuses on the development of an interactive digital e-module on Thaharah (Wudhu) using the ADDIE instructional design model, aimed at enhancing the learning experience of MTs (Junior High School) students. The e-module was designed as an interactive flipbook incorporating textual explanations, images, instructional videos, and interactive quizzes to support conceptual understanding and learner engagement. The ADDIE model—comprising the phases of Analysis, Design, Development, Implementation, and Evaluation—provided a structured framework for systematic instructional media development. A trial implementation was carried out at the UIN Palangka Raya campus, involving Islamic Education Study Program students who acted as representative MTs learners. Evaluation results indicated that the e-module is user-friendly and pedagogically effective, leading to improved comprehension of wudhu principles and increased student motivation. Participant feedback highlighted the module’s potential as an engaging and accessible tool for delivering technology-integrated Islamic religious education. These findings affirm the relevance of interactive digital media in supporting curriculum delivery and learner-centered pedagogy in religious education contexts.